2019
DOI: 10.3390/su11205851
|View full text |Cite
|
Sign up to set email alerts
|

Workforce Ageing and Labour Productivity in Europe

Abstract: This article analyses the influence of workforce ageing on labour productivity in Europe. This question is relevant because of the impact it may have on economic activity, social security systems sustainability and the wellbeing of the population. The method applied is a quantitative contrast using the panel data technique for 24 countries in the period 1983–2014. This research is framed in the open conversation in the literature on the possible impact of ageing on productivity and takes as reference the semin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In addition to the mixed evidence on how productivity evolves with age, previous literature provides mixed evidence on how aging affects productivity at the micro-level (worker's productivity) and at the macro-level (aggregate productivity). Calvo-Sotomayor, Laka, and Aguado [26] provided evidence that an increase in the older workforce reduced an increase in productivity, but the influence would be less observed due to the development of capital and knowledge-intensive sectors. Mahlberg et al [27] also reported that a larger share of older employees was not associated with reduced productivity at the firm level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the mixed evidence on how productivity evolves with age, previous literature provides mixed evidence on how aging affects productivity at the micro-level (worker's productivity) and at the macro-level (aggregate productivity). Calvo-Sotomayor, Laka, and Aguado [26] provided evidence that an increase in the older workforce reduced an increase in productivity, but the influence would be less observed due to the development of capital and knowledge-intensive sectors. Mahlberg et al [27] also reported that a larger share of older employees was not associated with reduced productivity at the firm level.…”
Section: Introductionmentioning
confidence: 99%
“…The connections between population aging and economic growth are complicated. Various authors [ 27 , 96 , 97 , 98 , 99 ] argue that there are multiple factors that influence growth both positively and negatively. On the one hand, among the factors holding back growth are, for example, periods of war, financial crises or demand shocks.…”
Section: Myths Beliefs Challenges and An Open Questionmentioning
confidence: 99%
“…They point out a negative and significant effect between these two variables. A recent research on Aiyar, Ebeke and Shao’s work, even if it also identifies this negative relationship for the period 1983–2014 in European countries, also presents some new questions about the evolution and possible disappearance of the effect of population aging on labor productivity during the 1995–2004 decade [ 99 ]. Anyhow, the literature investigating a possible relationship between population ageing and aggregate productivity is "surprisingly small" [ 107 ] (p. 3).…”
Section: Myths Beliefs Challenges and An Open Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-temperature or highly humid work environment and long-term physical workload expose workers to chronic fatigue, injury, illness, and health risk, and thereby reduce a site’s productivity [ 6 , 7 ]. An increase in the number of older workers, that is, aging of the construction workforce, has also been reported to affect the productivity of the construction industry [ 8 , 9 ]. Concerning the fatality rate in this industry, the U.S. Bureau of Labor Statistics reported that, between 2003 and 2010, more than 43,000 people experienced fatal accidents at the construction site [ 10 ].…”
Section: Introductionmentioning
confidence: 99%